SOFTWARE RETAILERS FROM BRAŞOV AND THE ONLINE STORES - Axenia Bianca BOITOR (Management & Marketing)
This paper presents the factors that influence the online marketing strategies of software vendors from Braşov County. An analysis of the software retailers’ attitudes from Braşov regarding online marketing and advertising was made. A survey among vendors from Braşov was undertaken and the results of this research show an orientation of lesser extent to online sales and marketing of the retailers’ activity. 20 responses were collected from software companies which trade software products and services in Braşov County. The results are very important for the companies that sell software products and services not only on the local market but also at national level. The paper presents the main reasons why software retailers from Braşov County, which is one of the most developed software markets in the country, have a lesser orientation towards online selling of software products and services. More than 400 companies involved in the software domain operate in Braşov City only. Research questions regarding the effects of the present economic situation, the online marketing strategies used in the software industry, and details about the online activity of each company where part of this research.